Application of specialised knowledge in proceedings concerning defence land - A. V. Shulzhenko (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the analysis of proceedings relating to defence land. Such proceedings are connected with the return of illegal use of state-owned land in accordance with its intended purpose. Based on a study of the Unified State Register of Court Decisions, it has been established that at least five lawsuits per region are filed annually by municipal maintenance departments representing the Ministry of Defence of Ukraine with commercial courts. As a result of the resolution of court disputes in this regard, only one third of the claims are satisfied. The reasons for this state of affairs have been analysed.